Balamuthia mandrillaris Granulomatous Amoebic Encephalitis: The First African Experience. Issue 12 (30th August 2022) - Tootla, Hafsah D; Eley, Brian S; Enslin, Johannes M N; Frean, John A; Hlela, Carol; Kilborn, Tracy N; Moodley, Bhavani; Peer, Shazia; Singh, Shivani; Nuttall, James J C
Abstract: We report the first case of Balamuthia mandrillaris granulomatous amoebic encephalitis definitively acquired in Africa. Our case emphasizes initial nonspecific dermatological features, delays in confirmation of the diagnosis, difficulties accessing recommended medication, and uncertainty about optimal treatment of a disease with a frequently fatal outcome.